2017
DOI: 10.1007/s00606-017-1440-9
|View full text |Cite|
|
Sign up to set email alerts
|

Third release of the plant rDNA database with updated content and information on telomere composition and sequenced plant genomes

Abstract: Here we present the third release of the plant rDNA database (March 2017), an open access online resource with information on numbers, locations and structure of 5S and 18S-5.8S-26S (35S) ribosomal DNA (rDNA) (www.plantrdnadatabase.com). Data are now available for 2,148 species (3,783 entries), extracted from 785 papers published until the end of 2016. This means an expansion of 33.5% in terms of new species and 13% in new publications consulted. We appreciate an increased interest on rDNA loci research in rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…Despite all the telomere motif exceptions detected, the real diversity in telomeric sequences in land plants is probably greatly underestimated. A recent publication (Vitales et al, 2017), in which a screening of land plant telomere sequences was performed, found that telomere sequences were only known clearly for less than 10% of the species and 40% of the genera contained in the Plant rDNA database (www.plantrdnadatabase. com), a resource providing molecular cytogenetics information on land plants (Garcia et al, 2012).…”
Section: How Variable Are Telomere Sequences?mentioning
confidence: 99%
“…Despite all the telomere motif exceptions detected, the real diversity in telomeric sequences in land plants is probably greatly underestimated. A recent publication (Vitales et al, 2017), in which a screening of land plant telomere sequences was performed, found that telomere sequences were only known clearly for less than 10% of the species and 40% of the genera contained in the Plant rDNA database (www.plantrdnadatabase. com), a resource providing molecular cytogenetics information on land plants (Garcia et al, 2012).…”
Section: How Variable Are Telomere Sequences?mentioning
confidence: 99%
“…Molecular cytogenetic mapping of the nuclear ribosomal RNA genes encoding for 35S (18S-5.8S-25S) and 5S rDNAs have proved useful for identifying the patterns and dynamics of chromosomal changes in closely related species groups (Jang et al, 2013(Jang et al, , 2016aVitales et al, 2017). The distribution of rDNA loci has been reported for some Korean monocots, as summarized in Table 1 (data retrieved from Plant rDNA Database; http:// www.plantrdnadatabase.com/, 2018 May 22).…”
Section: Patterns Of Genome Evolution: the Use Of Molecular Cytogenetmentioning
confidence: 99%
“…The chromosome numbers in Korean non-Commelinids monocots have previously been reported for a number of taxonomically closely related taxa (Rice et al, 2015, references therein), although the incidence of polyploids and its evolutionary aspects have not been addressed in detail. It is therefore timely to summarize the knowledge of chromosome numbers, genome sizes, and polyploidy incidence in the Korean monocots (Rice et al, 2015;Vitales et al, 2017) and to identify the most important taxonomic groups in which questions of chromosomal evolution can be addressed most effectively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5S rDNA contains a highly conserved coding region of 120 bp and a non-transcribed spacer (NTS region that varies between 100 and 900 bp). As relatively stable and reliable molecular cytogenetic markers, the characteristics of 45S and 5S rDNA on chromosomes provide useful information for chromosome research [27][28][29]. The FISH positions of rDNAs on chromosomes directly provide an effective method for chromosome identi cation and the research of chromosome organization and evolution.…”
Section: Introductionmentioning
confidence: 99%